2017
DOI: 10.1017/s1041610217000102
|View full text |Cite
|
Sign up to set email alerts
|

Multiple category verbal fluency in mild cognitive impairment and correlation with CSF biomarkers for Alzheimer's disease

Abstract: Animal fluency alone and combined to FAS-COWA was slightly superior in discriminating controls from MCI (p < 0.001), and correlated to T-tau levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 28 publications
3
19
0
1
Order By: Relevance
“…Their findings underpin the observation that category fluency deficits (together with episodic memory deficits) are the only consistent early deficits in individuals with MCI who progress to AD . A recent study shows that cerebrospinal fluid biomarkers (specifically T‐tau) were negatively correlated with animal fluency but were not significantly correlated with measures of phonemic fluency …”
Section: Discussionmentioning
confidence: 94%
“…Their findings underpin the observation that category fluency deficits (together with episodic memory deficits) are the only consistent early deficits in individuals with MCI who progress to AD . A recent study shows that cerebrospinal fluid biomarkers (specifically T‐tau) were negatively correlated with animal fluency but were not significantly correlated with measures of phonemic fluency …”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have proven that there are significant differences in the results of verbal fluency test, especially semantic fluency, between normal elderly and elderly with MCI. Elderly with MCI showed lower verbal fluency test results [30][31][32]. Verbal fluency is a cognitive function that allows retrieval of information from memory stored in the brain by involving executive functions and language skills.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The cutoff score for differentiating those with vascular disease from normal participants was ≤ 3. Mirandez [19] found that the cutoff score for the animal category test of VF was 14, and the AUC = 0.794. In comparison, Brucki et al [20] found that the cutoff points were 9 for people with less than 8 years of education and had a mean of 13 for those with higher educational levels.…”
Section: Discussionmentioning
confidence: 99%